2019
DOI: 10.4183/aeb.2019.460
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Insulin, Heparin and Fenofibrate Combination Treatment in Severe Hypertriglyceridemia: Double Center Experience

Abstract: Context.Severe hypertriglyceridemia (SH), which calls for a triglyceride (TG) level above 1000 mg/dL, remains an important health issue. While some data exist to offer combination of heparin, insulin and fenofibrate as a reasonable treatment option, safety and benefits of this therapy have not been accurately weighted, largely due to the limited sample size of the relevant studies.Aim. Assess the efficacy and safety of the heparin, insulin and fenofibrate combination in the treatment of patients with SH.Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In accordance with previous studies conducted in non-pregnant women ( Ladizinski and Lee, 2013 ; Soliman, 2021 ), our research indicates that insulin drip can reduce the level of TGs and TCs effectively and safely and might become a shining star in the treatment of HTG in this sensitive period. By stimulating lipoprotein lipase (LPL) synthesis and activity, which gives a subsidy to the degradation of VLDL chylomicron to glycerol and free fatty acids, and inhibiting hormone-sensitive lipase in adipocytes, the key enzyme for decomposing adipocytes’ TGs into free fatty acids, insulin reduces the serum triglyceride level rapidly ( Ozcelik et al, 2019 ). The results of our study demonstrated that an average decline of TGs is around 8.82 mmol/L on the condition of the mean length of hospital stay of 6.71 days, while the peak of discrimination of TGs before and after treatment is 48.65 mmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous studies conducted in non-pregnant women ( Ladizinski and Lee, 2013 ; Soliman, 2021 ), our research indicates that insulin drip can reduce the level of TGs and TCs effectively and safely and might become a shining star in the treatment of HTG in this sensitive period. By stimulating lipoprotein lipase (LPL) synthesis and activity, which gives a subsidy to the degradation of VLDL chylomicron to glycerol and free fatty acids, and inhibiting hormone-sensitive lipase in adipocytes, the key enzyme for decomposing adipocytes’ TGs into free fatty acids, insulin reduces the serum triglyceride level rapidly ( Ozcelik et al, 2019 ). The results of our study demonstrated that an average decline of TGs is around 8.82 mmol/L on the condition of the mean length of hospital stay of 6.71 days, while the peak of discrimination of TGs before and after treatment is 48.65 mmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin is reputed to curb the degree of diabetes. Unexpectedly, by stimulating LPL synthesis and activity, which gives a subsidy to the degradation of VLDL chylomicron to glycerol and free fatty acids, and inhibiting hormone-sensitive lipase in adipocytes, the key enzyme for decomposing adipocytes TGs into free fatty acids, insulin introduces reduced serum TG level rapidly 12 . It is remarkable that there seemed rebounds after insulin therapy and only with once more insulin drip can her TG and TC reduced again; therefore, it came to a conclusion that intravenous insulin drip is laced with benefits temporarily.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin has been documented as an effective lowering-lipid levels regime until a woman who use heparin chronically was found to progress AP because heparin depleted the LPL on the surface of the endothelial cells and spelled a hypertriglyceridemic effect 11 . After that, more cases of HTG secondary to employment of heparins have been reported; therefore, its use is not recommended 4,12 . Despite plasmapheresis therapy was observed to reduce serum TG levels effectively when severe GHTG was refractory to all other regimens, its widespread employment has been restricted by its high-cost, catheter associated inflammation, biological availability, and risks of thromboses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It accounts for 10% of all cases [ 1 ]. Treatment of hypertriglyceridemia involves lowering lipid levels by enhancing lipoprotein lipase activity through insulin infusions/plasmapheresis/heparin and/or fibrate therapy [ 2 ]. The removal of triglycerides via plasmapheresis was first described by Betteridge in 1978 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%